SELECTION OF MICROBIAL ISOLATES BASED ON PECTINASE ENZYME ACTIVITY AS A STARTER IN OPTIMIZING WEST JAVA ARABICA COFFEE FERMENTATION - Amanda Isak Taib, Nissa
Coffee is an agricultural commodity that is widely traded in international markets. However, despite being the fourth largest coffee exporter in the world, coffee processing in Indonesia—especially in fermentation—has not been carried out in a controlled manner. The fermentation process in coffee aims to degrade the slime layer containing pectin in order to improve the taste of coffee, so that controlled fermentation is important to ensure that the microbes that grow are microbes that support pectin degradation and produce the desired metabolites. The purpose of this study was to obtain potential microorganisms as starters based on the selection of pectinase enzyme activity to help improve the taste of West Java Arabica coffee; determining microbial population dynamics during controlled fermentation of coffee; as well as determining the microbial starter formulation based on the best coffee cupping test value. Selection of starter candidates for yeast and bacteria isolates was carried out based on pectinase activity qualitatively and quantitatively. The selected isolates were then harvested for starter production. Controlled fermentation of coffee was carried out by adding a starter that had variations in the ratio of yeast and bacteria 1:0, 0:1, 1:1, and no starter was added as a control for 72 hours. Sampling was carried out for microbial enumeration and pH measurement every 12 hours. The organoleptic test was carried out using the cupping test method by a certified coffee institution. The yeast isolates with the highest total pectinase activity were R1-TKSU with a value of 7.187 ± 0.115 u/mL on Synthetic Pectin Media (SPM) and 5.341 ± 0.063 u/mL on Coffee Pulp Media (CPM) and bacterial isolate B1-DKBB with a value of 8.177 ± 0.392 u/mL on SPM and 5.04 ± 0.064 u/mL on CPM. As a result, the total microbial enumeration showed that the starter isolate dominated the microbial abundance and the coffee added by the starter with a 1:0 ratio of yeast and bacteria showed the highest cupping test value.